DEKOMPOSISI SERASAH MANGROVE Avicennia alba KONTRIBUSINYA TERHADAP NUTRIEN PERAIRAN DI DESA BAGAN ASAHAN KECAMATAN TANJUNGBALAI KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Nur Hidayah Nasution; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2017)
Organic mangrove material is mostly used as a detritus such mangrove leavesthat fall throughout the year. Organic particles or litter become living places for bacteria, fungi and other microorganisms. The objective research was to measure decomposition and know the nutrient content of carbon (C) nitrogen (N) and phosphorus (P) leaf litter A. alba released during decomposition in Bagan Asahan Village, Tanjungbalai Sub-district of Asahan Regency. The study was conducted from February to April 2017 using purposive sampling method by looking availability of A. alba Bagan Asahan Village. Result of highest carbon nutrient content (C) station I 18,85% lowest station III 11,58%. The highest nitrogen (N) station III 2, 62% lowest station II 2,29%. The highest phosphorus (P) with the same value station III 0,03% lowest station II 0,01%. Highest C/N station results station III 6,44% lowest station II 4,70%. Dry weight of litter decreased period during the 90 days of the highest average station II 21,70 g lowest station II 2,13 g compared with the initial weight of 50%. The highest value decomposition rate between station III 2,81 lowest value 0,52. The highest average value decomposition rate (k) station I e.i. 41,70 lowest station III e.i. 1,66.Keywords: Avicennia alba, Bagan Asahan Village, Decomposition, Element Nutrient, Leaf Litter, Mangrove.